Antimicrobial Activity and Chemical Composition of Essential Oil Extracted from Solidago canadensis L. Growing Wild in Slovakia - Elshafie, Hazem S. (Molecules, 2019)
Plant essential oils (EOs) are one of the most relevant natural products due to their biological, medicinal, and nutritional properties. The promising biological effects of many plants EOs encourage researchers to study their biochemical properties to be used as possible natural alternatives for commercial pesticides and not only as herbal medicines. The current research has been conducted to study the microbicide effect of Solidago canadensis L. EO to control some common plant diseases caused by several postharvest phytopathogenic fungi (Monilinia fructicola, Botrytis cinerea, Aspergillus niger, and Penicillium expansum) in comparison with Azoxystrobin as a large spectrum fungicide. The antibacterial activity has been carried out against some phytopathogenic bacteria (Bacillus megaterium and Clavibacter michiganensis (G+ve) and Xanthomonas campestris, Pseudomonas fluorescens, and Pseudomonas syringae pv. phaseolicola (G−ve)) compared to the synthetic antibiotic Tetracycline. Minimum inhibitory concentration was carried out to determine the lowest effective EO dose using a 96-well microplate. The cell membrane permeability was also evaluated by measuring the electric conductivity (EC) to examine the possible mechanisms of action of S. canadensis EO. Chemical characterization of EO has been carried out using gas chromatography and mass spectrometry (GC-MS). Thirty-two identified components in S. canadensis EO presented 97.7% of total compounds in EO. The principal compounds were identified as germacrene D (34.9%), limonene (12.5%), α-pinene (11.6%), β-elemene (7.1%), and bornyl acetate (6.3%). In addition, S. canadensis EO demonstrated promising in vitro antimicrobial activities against the majority of tested phytopathogens at all tested concentrations.